Percepções de um contrato racial na trajetória educacional dos negros no Brasil: estudo a partir da representatividade dos negros no município de Concórdia, SC - Velho, Bruna Marcos (2020)
This research focuses on the educational trajectory of blacks in Brazil and discusses racial ethnic issues that evidence the presence of a Racial Contact involving the Brazilian Afrodescendant population. However, due to the scope of the theme, the research took as reference the municipality of Concórdia, SC., and sought to understand the relationship between education and the degree of representation of blacks in this municipality. The objective of the study, therefore, consists of perceiving formal education actions and reactions in face of the genesis and consequences of the subjugation processes of blacks in different social segments, which occurred from the colonial period to the present. In this sense, following the thesis defended by Charles W. Mills (1997) that points out the Racial Contract (The Racial Contract) as a political, moral and epistemological device that marks a historical reality of exploitation legitimized by the nation-state, this research debates the implications of Law 10,639 of 2003 (changed to Law 11,645 of 2008) and seeks to answer the following questions: a) to what extent do Brazilian educational processes and policies reveal the presence of a Racial Contract in the educational trajectory of blacks in Brazil ?; b) considering the educational reality and the representativeness of blacks in the municipality of Concórdia, SC., under what circumstances and proportions are possible the correspondences between education, representativeness and overcoming prejudices? With regard to the methodological procedure, the research is structured in the bibliographic / documentary analysis, through authors who address the history of access to education for the black population in Brazil and the laws that established the guidelines and bases of national education to include in the curriculum official of the education network the mandatory theme "History and AfroBrazilian and indigenous culture". In addition, the research has an empirical investigation with representatives from different social segments in the municipality of Concórdia, and in three institutions: Municipal Education Department; Regional Education Coordination; and in the black organization of the municipality (NIARA/OSCIP). Data interpretation is based on the Content Analysis methodology, developed by Laurence Bardin. The analysis and interpretation of the interviews and other approaches on the topic were carried out through the categorization process. That is, the comprehension of the research results is associated with the categories of analysis that emerged before and after the interviews. Finally, it is important to say that, despite the complexity of the theme and the science of continuous critical reflection on it, this research can verify that racism, that veiled, masked and naturalized, perceptive in pejorative speeches, discriminatory looks etc., made structural in Brazilian society and needs to be discussed. This finding extends to the municipality of Concordia/SC., and was made noticeable, mainly, through the interviewees' statements. Therefore, turning to the educational trajectory of blacks in Brazil, with a Brazilian municipality as the place of research on the representativeness of blacks, proved to be a fruitful condition for us to debate on the subject, as well as to deepen the other questions proposed by the research.